Virological characteristics of the SARS-CoV-2 Omicron BA.2.75 variant - Saito, Akatsuki; Tamura, Tomokazu; Zahradnik, Jiri; Deguchi, Sayaka; Tabata, Koshiro; Anraku, Yuki; Kimura, Izumi; Ito, Jumpei; Yamasoba, Daichi; Nasser, Hesham; Toyoda, Mako; Nagata, Kayoko; et al. (Cell host & microbe, 2022)
The SARS-CoV-2 Omicron BA.2.75 variant emerged in May 2022. BA.2.75 is a BA.2 descendant but is phylogenetically distinct from BA.5, the currently predominant BA.2 descendant. Here, we show that BA.2.75 has a greater effective reproduction number and different immunogenicity profile than BA.5. We determined the sensitivity of BA.2.75 to vaccinee and convalescent sera as well as a panel of clinically available antiviral drugs and antibodies. Antiviral drugs largely retained potency, but antibody sensitivity varied depending on several key BA.2.75-specific substitutions. The BA.2.75 spike exhibited a profoundly higher affinity for its human receptor, ACE2. Additionally, the fusogenicity, growth efficiency in human alveolar epithelial cells, and intrinsic pathogenicity in hamsters of BA.2.75 were greater than those of BA.2. Our multilevel investigations suggest that BA.2.75 acquired virological properties independent of BA.5, and the potential risk of BA.2.75 to global health is greater than that of BA.5. [Display omitted] •BA.2.75 is more transmissible than BA.5•Immunogenicity of BA.2.75 spike is different from that of BA.2 and BA.5•Compared with BA.2, BA.2.75 exhibits higher affinity to ACE2 and greater fusogenicity•In infected hamsters, BA.2.75 exhibits greater pathogenicity than BA.2 Saito and G2P-Japan Consortium et al. elucidate the virological properties of the SARS-CoV-2 Omicron BA.2.75 variant. BA.2.75 is more transmissible than BA.5 and exhibits different antigenicity than BA.2 and BA.5. The BA.2.75 spike exhibits higher affinity to ACE2 and higher fusogenicity, and BA.2.75 is more pathogenic than BA.2 in hamsters.